Alfabetización digital de ciudadanos habitantes de calle: una experiencia de ecología de saberes - Gil, Yeison A. (2020)
The purpose of this document is to present the results of the digital literacy process, which was implemented through the program called "Sistemas básicos” aimed at street dweller citizens (CHC, in Spanish) of the city of Bogotá DC, whose primary objective was to strengthen the development of capacities of the participants in the use of computers, new technologies and ICT, and additionally, to strengthen the pedagogical practices of educators, consolidating a dynamic of ecology of knowledge between them. Therefore, this initiative seeks to respond to the social, cultural and psychological relationships and conditions of the participants from the teaching task in the classroom. Thus, the main hypothesis is framed in that the implementation of the “Sistemas básicos” program, through an experiential methodology oriented from the pedagogical practice of the ecology of knowledge, allows to achieve a successful training process in the CHC, overcoming digital gaps, psychological, social and motor affectations by the consumption of psychoactive substances, the habitability in the street and the low or no academic training of these citizens. The strategy is developed, moreover, not for them to forget to put aside everything they have experienced as street dwellers, but rather to be able to establish a dialogue from the practices assimilated and lived on the street, and the proposed personal development processes by care and development programs.